Correlation of wrist circumference with waist circumference and body mass index in adults with early-onset type 2 diabetes mellitus - V., Ajithkumar P.; L., Manju; M., Deepa (International Journal of Research in Medical Sciences, 2019)
Background: Recent studies have shown that wrist circumference is correlated with insulin resistance, obesity and new onset diabetes. Being easy to measure, it may be useful in identifying individuals at risk for cardio- metabolic disorders. Methods: 112 consecutive subjects with new onset type 2 diabetes in the age group 18-44 years were included in the study. Socio demographic characteristics, anthropometric and biochemical measurements were carried out using standard techniques. Pearson product movement Correlation Coefficient was used to find out correlation with other measures of obesity and ROC curve to determine its cut off values. Results: Wrist circumference showed moderate positive correlation with BMI (r+0.389) and waist circumference (r+0.443). The cut off value of wrist circumference when compared with BMI in defining obesity was 16.5cm in male and 15.7 cm in female. The cut off value of wrist circumference with waist circumference in male was 16.2cm. Conclusions: Measurement of wrist circumference may supplement in assessing obesity especially when other measures of obesity like BMI or Waist circumference measurements are difficult or not feasible.